Construct validity and measurement invariance of the Asian Family Characteristics Scale in the Thai population - Thipnapa Huansuriya; Piyakrita Kruahiran; Suppanut Sriutaisuk; Ramli Musa (College of Public Health Sciences, Chulalongkorn University, 2022)
Purpose - The purpose of this paper was to establish the psychometric properties of the Asian Family Characteristics Scale (AFCS) in the Thai population. Design/methodology/approach - The 30-item AFCS originally developed in the Malay language was translated into Thai. Thai (n = 384) and Malay (n = 500) participants in Study 1 responded to the AFCS in their respective languages. The data were subjected to a confirmatory factor analysis with a measurement invariance test. In Study 2, Thai participants (n = 495) filled out the AFCS and Chulalongkorn Family Index, International Personality Item Pool-NEO, Self-Compassion Scale, Depression, Anxiety, and Stress Scale (DASS-21) and Satisfaction with Life Scale. Findings - Study 1 showed that the measurement model of the Thai AFCS fit the data from the Thai population. The measurement invariance test confirmed that the structure and meaning of the AFCS are equivalent across the Thai and Malay samples. Study 2 demonstrated the AFCS's convergent validity by showing that the AFCS score had a positive correlation with the Chulalongkorn Family Inventory, self-compassion, agreeableness, conscientiousness, satisfaction with life and a negative correlation with neuroticism, depression, anxiety and stress. The AFCS's discriminant validity was supported by nonsignificant correlations with extraversion and openness to experience. Originality/value - This paper is an attempt to develop a family characteristic measure specifically for the Asian population. The results provide empirical evidence for measurement invariance and validity of the scale in another Asian language, enhancing its cross-cultural generalizability.